Talk:Relativity: The Special and General Theory

From Wikisource
Jump to: navigation, search
Information about this edition
Edition:
Source: Gutenberg etext 5001 and marxists.org(Methuen & Co Ltd; 1920); bartleby 173 (Henry Holt and Company, 1920),
Contributor(s):
Level of progress:
Notes:
Proofreaders:

There appear to be a number of gif files that are not being loaded into the document, as there are ".gif" placeholders in various notes sections. Are they missing equations? If so, this document is rather uselss. Can someone else explain this? --Exlibris 20:28, 20 May 2005 (UTC)

It seems the text is just copied from somewhere and the author did not care to make it loog good on wikisource. 59.93.129.1 14:16, 2 September 2005 (UTC)

That begs the question. There are presumably gif files with the equations in them. So where are they? Otherwise why come-up with names for said files and insert them into the document? For the sole purpose of confusing the rest of us? --Pdelong 04:04, 16 November 2005 (UTC)

Here's the whole text, published under the GFDL. http://www.marxists.org/reference/archive/einstein/works/1910s/relative/ I have corrected some of the equations, but won't have time to do the rest in a while. --Olofos 15:20, 18 December 2005 (UTC)

Can't we just use the math tags, and do it in LaTeX? 129.67.10.3 03:02, 15 January 2006 (UTC)
A LaTeX version is available here. Cheers, 71.125.151.219 13:04, 11 February 2006 (UTC)
The full book including equations should still be findable on the net in "Windows HelpFile" hypertext, as a file called relativ.hlp. [1] Just tried downloading it, it all still seems to be there. Not much good unless you have Windows, tho' :( ErkDemon 05:25, 19 December 2006 (UTC)
Here's a PDF version: www.relativitybook.com ErkDemon (talk) 22:50, 12 June 2009 (UTC)

License and translator?[edit]

Hello,

This text is missing a license and the translator's name. Yann 11:03, 2 November 2007 (UTC)

Done. - Mtmelendez 16:00, 17 June 2008 (UTC)

The derivation of Lorentz transformation is wrong![edit]

In the derivation Einstein offers two opposite arrangements;


  • Arrangement (I)


A light signal which is proceeding along the positive axis of x (to the right) giving the following results:

x = c t (or c = x /t)

x' = c t' (or c = x'/t')

i.e.

x − c t = 0 ..................(1)

x' − c t' = 0 ..................(2)

and

(x' − c t') = λ(x − c t)..........(3)


  • Arrangement (II)


If we apply quite similar considerations to light rays which are being transmitted along the negative x-axis (to the left)

x = - c t (or c = - x /t)

x' = - c t' (or c = - x'/t')

i.e.

x + c t = 0

x' + c t' = 0

and

(x' + c t') = μ(x + c t).............(4)


  • Notes on the introduction of λ and μ


1) Equation (3) holds true even if λ = 1

2) Equation (4) holds true even if μ = 1


  • Restrictions on the values of X, X'


(You can ignore this section if you are bored, it only provides the logic behind uncovering Einstein's blunders, the real blunders are in the next section)

1) Frame k' is moving with a relative speed of (v) compared to frame (K), this speed is along the positive x-axis, i.e. to the right as indicated in fig.2 of section 11

2) Arrangement (I) introduces a light signal moving in the same direction of (v) with an absolute speed (c), while the light signal of arrangement (2) is moving in the opposite direction of (v) with the same absolute speed (c)

3) Accordingly, all equations of arrangement (I) hold true only for positive values of x,x' (because light is moving along positive x-axis), otherwise if we measure the speed of light we will find that: (c = x/t = x'/t')< 0, i.e. c is negative and the light signal would be moving in the opposite direction of (v), and along the positive x-axis in the same time, which is obviously a contradiction

4) Similarly, all equations of arrangement (II) hold true only for negative values of x,x' (because light is moving along the negative x-axis), otherwise if we measure the speed of light we will find that: (c = - x/t = - x'/t')< 0, i.e. c is negative and the light signal would be moving in the direction of (v), and along the negative x-axis in the same time, which is also a contradiction

5) These restrictions are necessary to avoid contradictions, but we will find that Einstein was not aware of them when he proceeded to the next step

Einstein's next step was to combine these two arrangements into on equation:


  • Combining Arrangements (I) and (II)


We have so far

(x' − c t') = λ(x − c t) ................(3)

(x' + c t') = μ(x + c t) ................(4)

but each of these equations is restricted to a separate arrangement, with restricted values of x,x', He however choose to add or subtract the equations ignoring the hidden contradictions, giving the following equations:

after also substituting

a = (λ + μ) / 2

b = (λ - μ) / 2

we get

x' = a x - b c t ..........(5a)

c t' = a c t - b x ............(5b)


  • Notes on combining arrangements (I), (II)


1) Now that Einstein has combined these two arrangements, treating them as parts of a single system, the contradictions will be much more obvious, as in his steps to reach equations (5a) and (5b), he used the following equations, and now he assumes that all of them are true concurrently:

x = c t (or c = x /t)...............(fucked up equation 1)

x' = c t' (or c = x'/t')..............(fucked up equation 2)

and

x = - c t (or c = - x /t)............(fucked up equation 3)

x' = - c t' (or c = - x'/t')...........(fucked up equation 4)


Substituting c t = x from (fucked up equation 1) in (fucked up equation 3) we get:

x = - x

and accordingly

x' = - x'

If you are not surprised by now, then you understand nothing about math, these equations means:

if x = 1

then 1 = -1

if x = 2

then 2 = -2

Which is why I call them fucked up equations, the only condition when these equations hold true is when x = x' = 0, for all other values of x,x' you have nothing but nonsense.

2) If you think that you are smart and will say, that these equations are wrong because these equations belong to different arrangements, I will tell you sorry, it wasn't me who came up with the whole thing, it wasn't me who combined the two separate arrangements, it was your divine Einstein who decided to put the two arrangements in the same equation together (equations 5a and 5b)

3) A variation on the fucked up equations is the following:

c = - c

t = - t

t' = - t'

which all holds true only if c, t , t' = zero, now you have no speed of light, no time variation, we have nothing at all.

4) Ignoring all of these blunders let's see how Einstein chooses to not see them and proceed in his next step, which is more fucked up, because he tries to evaluate his constants at the only working conditions, (i.e. when any of x,x',t,t' =0)


  • Einstein's evaluation


so far we have:

x' = a x - b c t ..........(5a)

c t' = a c t - b x ............(5b)

I actually suspects that Einstein knew that his equations is fucked up, because the following is just stupid.

He puts x'=0 (at the origin of k') in equation (5a) giving:

0 = a x - b c t

i.e.

x = b c t / a ...............(fucked up equation 5)

and he magically assumes that x/t = v (which could be true but not with his fucked up equations), then he gets

v = b c / a ..................(6)


  • Notes on Einstein's evaluation


1) He set x' = 0 alone, ignoring the corresponding values of the other variables (x,t,t',c), but if he thought carefully about it he would have found that according to his preliminary equations (the fucked up ones) :

c = x'/t'= - x'/t'= zero/t'= -(zero)/t' = 0

i.e.

if x'= 0 , then c = zero , but of-course light could never propagate at a speed of zero, so this what would this mean?, I don't know, you tell me, but let's continue

substituting c=0 in (fucked up equation 5)


x = b c t / a = b * 0 * t / a = 0 / a = 0

but if x = 0 and according to (fucked up equation 1)

x = c t

i.e. t = x/c = 0/c = 0

or t = x/c = 0/0 (you tell me what this means)

and if c = 0, then substituting it in equation (6) we have

v = b c/ a= b * 0/ a = 0 / a = zero

then if v = zero, the moving frame is not moving at all

2) To derive equation (6) Einstein assumed that v = x/t forgetting the fucked up equation 1)

c = x/t

does this means that c = v = x/t, i.e. c = v, a new revelation the moving frame is moving with the speed of light, though we have already established that it isn't moving at all


  • I think this is enough :)
As a comment, this is not an encyclopaedic work, nor do we profess it to be correct, or current. It is simply a work that is reproduced as of its original date of publication. — billinghurst sDrewth 07:33, 27 September 2010 (UTC)